Profile of Medical Radiation Science Practitioners as Lifelong Learners: Implications for the Design of Undergraduate Programs - Sim, Jenny (Curtin University, 2000)
Literature has shown the importance of lifelong learning in the training of today's workforce and the crucial role of Higher Education in preparing graduates for lifelong learning. The aim of the current study is to establish the profile of Medical Radiation Science (MRS) practitioners as lifelong learners and to examine the implications of these findings for MRS undergraduate programs in Australia. The study builds on Candy et. al.'s 1994 report, Developing Lifelong Learners through Undergraduate Education, by drawing on the report's profile of lifelong learners and the features of the undergraduate program that promote lifelong learning. This present study used both quantitative and qualitative approaches, including collating the stakeholders' views on lifelong learning via surveys, one-to-one interviews and focus group discussion.Findings from this study indicate that all stakeholders (MRS practitioners, Heads of MRS Departments, students and teaching staff) viewed lifelong learning to be relevant to the profession and are important attributes for MRS practitioners to attain. However, attributes that were directly related to clinical competencies were more highly valued than attributes which were perceived to be associated with learning competencies. For each of the 25 attributes surveyed, the actual level of attainment fell below the nominated level of importance. Furthermore, the workplace culture was found to be non-supportive of lifelong learning. All MRS courses in Australia promote lifelong learning as one of their course objectives. There is a general trend towards adopting teaching approaches that promote lifelong learning, while assessment methods that promote and evaluate lifelong learning attributes were lagging behind.These findings have implications for both the MRS workplace and the MRS undergraduate courses in Australia. There needs to be greater dialogue and collaboration between the MRS employers and the universities to address the gap identified in the attributes. A conceptual model integrating lifelong learning in the context of MRS has been introduced to circumnavigate the predicament felt by most respondents that clinical competency must take precedence over all other attributes. Selection criteria by employers for graduates who are entering the workplace for the first time serve as the vital link between the workplace and the universities. By incorporating lifelong learning attributes as an essential part of the selection criteria, students would come to see the relevance of lifelong learning in their undergraduate training. A learning portfolio can be used as a means of demonstrating that the appropriate learning has taken place. There needs to be a closer link between teaching and assessment by aligning the teaching of lifelong learning objectives and activities with the assessment methods. To this end, it is important that teaching staff must be provided with the appropriate professional support to cultivate lifelong learning attributes and to equip them with the appropriate facilitation skills, before the lecturers can be expected to adopt lifelong learning approaches. This research provides a snapshot of lifelong learning in the MRS profession and should assist in the implementation of lifelong learning strategies that would direct the future of the profession.